Artikel Kehormatan: Sengketa Penanaman Modal antara Investor Melawan Pemerintah di Arbitrase ICSID - Huala Adolf (Faculty of Law, Universitas Padjadjaran, 2014)
AbstrakPerhatian terhadap ICSID dewasa ini timbul kembali setelah beberapa investor menggugat pemerintah Indonesia di hadapan badan arbitrase ICSID. Tulisan ini mengupas konvensi yang melahirkan badan arbitrase ICSID, yaitu Konvensi ICSID atau Convention on the Settlement of Investment Disputes between States and Nationals of Other States. Tulisan ini memaparkan pula latar belakang pemerintah Indonesia meratifikasi konvensi, berbagai sengketa penanaman modal yang melibatkan pemerintah Indonesia, dan pelajaran yang dapat dipetik dari adanya gugatan-gugatan oleh investor.Kata kunci: Konvensi ICSID, sengketa penanaman modal, modal asing, putusan arbitrase, gugatan investor. Investment Disputes between Investors and Indonesian Government in the ICSID ArbitrationAbstractThe attention to the ICSID arose among scholars and practitioners following the claims brought by the foreign investors against the government of Indonesia to the ICSID arbitration. This article discussed the ICSID Convention or the Convention on the Settlement of Investment Disputes between States and Nationals of Other States. This article also examined the background Indonesia ratified the Convention, the disputes involving Indonesia in ICSID Arbitration, and the lesson learned from the claims.Keywords: ICSID Convention, investment disputes, foreign capital, arbitration award, investor claims.DOI: https://doi.org/10.22304/pjih.v1n3.a1